902 Antimicrobial Utilization Pattern in Respiratory Tract Infections Among Pediatric Population in Ajman, Uae. (October 2012) - Hassan, M; John, LJ; Hassan, M
Abstract : Background and Aims: Respiratory tract infection (RTI) among children is a leading cause of sickness among school children and parental absenteeism from work. It is associated with hospitalization and significant morbidity. Antimicrobials play an integral role in management of RTIs but irrational use is too common. Hence, this study aimed to determine the prescribing patterns of antimicrobials among children attending the outpatient department (OPD) of pediatrics in GMC Hospital, Ajman. Methods: A cross-sectional drug utilization study was conducted using the prescriptions from the medical records of patients (aged 0–12 years) diagnosed with RTIs during January 2011 at GMC Hospital, Ajman. The demographic data, clinical diagnosis and antibiotic prescription were analyzed using descriptive statistics (SPSS 19). Results: A total of 488 patients (20.2%) presented with RTI to the OPD of pediatrics. Male to female ratio was 1.24. Majority of the patients were Egyptians followed by Emiratis. Majority of children 225 (46%) were between 1–5 years of age. Combination of upper and lower respiratory tract infections (URTI & LRTI) accounted for 187(38%), URTI 208(23%), and LRTI 93(19%). The most frequently prescribed drug categories for treatment of RTIs was antimicrobial agents followed by symptomatic medications of which decongestants were the most prevalent. On average, the number of drugs per prescription was 3.86. The combination of amoxicillin + clavulanate and azithromycin were the most prescribed antimicrobials. Conclusions: Overall, prescriptions of antimicrobials among pediatric patients suffering from RTIs were appropriate. There is scope for further improvement through formulation of institutional antibiotic guidelines for common RTIs.